Estimation of the Continuous Pronation–Supination Movement by Using Multichannel EMG Signal Features and Kalman Filter: Application to Control an Exoskeleton - Zhang, Lei; Long, Jingang; Zhao, RongGang; Cao, Haoyang; Zhang, Kai (Frontiers in Bioengineering and Biotechnology, 2022)
The Hill muscle model can be used to estimate the human joint angles during continuous movement. However, adopting this model requires the knowledge of many parameters, such as the length and speed of contraction of muscle fibers, which are liable to change with different individuals, leading to errors in estimation. This paper established the back propagation neural network model based on surface ElectroMyoGraphy (sEMG) features and human movement angle. First, define the function of muscles in joint rotation, then place sensors on muscle tissues to gain sEMG and then construct a relation model between the surface sEMG features and the joint angle. As integrated electromyography information cannot be well reflected through a single electromyography feature, a feature extraction method combining time domain, frequency domain, and time-frequency domain was proposed. As the Degree of Freedom (DOF) of the pronation-supination movement was controlled by several muscles, it was difficult to make an angle prediction. A method of correcting estimation error based on the Kalman filter was raised to cope with this problem. An exoskeleton robot with one DOF was designed and put into the tracking experiment. The results show that the proposed model was able to enhance the estimation of joint angle during continuous pronation-supination movements